2020
DOI: 10.3389/fmicb.2020.574815
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Estuarine Ammonia-Oxidizing Communities to Constant and Fluctuating Salinity Regimes

Abstract: Aerobic nitrification is a fundamental nitrogen biogeochemical process that links the oxidation of ammonia to the removal of fixed nitrogen in eutrophicated water bodies. However, in estuarine environments there is an enormous variability of water physicochemical parameters that can affect the ammonia oxidation biological process. For instance, it is known that salinity can affect nitrification performance, yet there is still a lack of information on the ammonia-oxidizing communities behavior facing daily sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Salinity is generally assumed to be important for the community structures, abundances, and activities of canonical ammonia oxidizers in coastal ecosystems ( 58 , 59 ). Although numerous findings have revealed that the distributions of AOA and AOB ( 60 ) or comammox Nitrospira ( 12 , 30 ) correlated with salinity in different coastal environments, the results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity is generally assumed to be important for the community structures, abundances, and activities of canonical ammonia oxidizers in coastal ecosystems ( 58 , 59 ). Although numerous findings have revealed that the distributions of AOA and AOB ( 60 ) or comammox Nitrospira ( 12 , 30 ) correlated with salinity in different coastal environments, the results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the impact of estuarine pollutants on microbial communities remains uncertain, necessitating comprehensive analyses of environmental factors across various estuarine types to uncover their specific driving mechanisms. Furthermore, most studies indicate that salinity, temperature and nutrients are key indicators affecting bacterial community in estuaries ( Santos et al, 2020 ; Wu et al, 2022 ). However, the overall influence of different forms of carbon, nitrogen, and phosphorus on estuarine bacterial communities remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of their importance in nitrogen cycling and their potential use in ammonia removal, for instance through coupled nitrification–denitrification processes, AOA and AOB have been well-studied in various habitats, including oceans ( Francis et al, 2005 ; Sintes et al, 2015 ), estuaries ( Zheng et al, 2014 ; Smith et al, 2015 ), lakes ( Liu and Yang, 2021 ), soils ( Pester et al, 2012 ; Shen et al, 2021 ), and wetlands ( Wang et al, 2013 , 2019 ). For example, many factors have been shown to affect the composition and abundance of AOB and AOA, including pH, temperature, salinity ( Santos et al, 2020 ), ammonia concentration ( Taylor et al, 2012 ), nutrient levels ( Dai et al, 2018 ), competition ( French et al, 2021 ), and predators ( Kim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%